Pengaruh E-Commerce dan Kontrol Diri terhadap Perilaku Konsumtif Mahasiswa Politeknik Statistika STIS di Era Digital - Nandita, Ni Komang Diva Amalia Putri; Purwoto, Agus; Supiadi, Nugraha Wahyu Putra; Sinaga, Vhania Mutiara; Parhas, Zahwa Zalzabila (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Consumptive behavior refers to the tendency of individuals to consume goods excessively without careful consideration. This behavior is prevalent among the younger generation, particularly among students. This study aims to investigate the influence of e-commerce and self-control on the consumptive behavior of students at Politeknik Statistika STIS. The analysis is conducted using a sample of 94 students from the first to the third year at Politeknik Statistika STIS. The results are obtained using logistic regression and ordinal regression analysis. The findings indicate that the variables of student gender, all categories of self-control status, and all categories of e-commerce influence have a significant simultaneous effect on the consumptive behavior status of Polstat STIS students.